Shot put: Gill Jacko home training (2011)
This movie has been made by Jacko GILL himself (Maybe already looking for a movie maker carrier after shot put , ) and is really throwing a light on his very specific "home" training ! Strength and Speed ...and a little bit of fun ! (But also a very hard daily work !) Certainly quite different from the usual (boring) training videos you will find on the web and the usual theories on throws conditioning during the coaching Congresses